Working efficiency of extension field staff with regards to integrated pest management of cotton in district D. G. Khan, Punjab, Pakistan - Adeel, Muhammad; Siddiqui, Badar Naseem; Tareen, Waqar-Ul-Hassan; Rayit, Adnan; Fahd, Shah (Journal of Pure and Applied Agriculture, 2023)
In the agriculture sector, the success of any program and project depends upon the working efficiency of extension field staff (EFS). EFS are key stake holders and play crucial roles in the extension services, particularly in agriculture and rural development. Therefore, the present study was conducted to evaluate the working efficiency of extension field staff with special reference to IPM of cotton growers in district D. G. Khan. The results reveal that most of the respondents (44.2%) were under 35 years of age and about 80.80% of them were educated. A majority of the respondents (85%) had small land holding up to 12.5 acres. Less than half of the respondents (42.5%) reported that EFS provided extension services fortnightly. More than half of the respondents (56.7%) reported that EFS provided excellent information regarding resistant varieties. About 69.2 to 84.2% of the respondents reported that microorganisms, beneficial insects, buying and releasing beneficial insect and protecting beneficial insects were poorly addressed. Insecticidal soap and horticultural oil were the activities that performed poorly by the EFS as reported by a vast majority (90%) of the respondents. More than half of the respondents (56.7%) were of the view that the time involved was a big problem in applying IPM. The entire respondents (99.2 -100%) were of the view that IPM had positive impact on their crops. So the concerted efforts such as launching of IPM program for cotton crop in other districts of Punjab, Pakistan should be made with the aim of adopting cultural and biological control rather than chemical control.